2010
DOI: 10.1590/s1806-66902010000300001
|View full text |Cite
|
Sign up to set email alerts
|

Formas de aplicação de nitrogênio em três cultivares de girassol na savana de Roraima

Abstract: -Nitrogen is the nutrient that limits most the production in the culture of sunflower (Helianthus annuus L). The nutritional requirements among cultivars of the same species is distinct, under the same conditions of culture and for the same agricultural year. With the objective of evaluating four different ways of nitrogen application in the production components of different genotypes of sunflower, an experiment was carried out in a randomized block design in a 3 x 4 factorial scheme (genotypes x ways of nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
13

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
(20 reference statements)
0
8
0
13
Order By: Relevance
“…Although lower than 19.9 and 22.4 cm, obtained by Lobo and Grassi Filho (2007) in the soil without and with 50 kg ha -1 of N, these values surpass the value of 11.9 cm in the capitulum diameter of the sunflower cultivar H358 at the dose of 44.9 kg ha -1 of N reported by Biscaro et al (2008). In this context, Ivanoff et al (2010) claim that adequate N fertilisation management promotes increments of approximately 16% in the mean diameter of sunflower capitulum; this was also observed by Siddiqui et al (2009) …”
Section: Figure 2 Number Of Viable Achenes In Sunflower CV "Embrapamentioning
confidence: 48%
See 1 more Smart Citation
“…Although lower than 19.9 and 22.4 cm, obtained by Lobo and Grassi Filho (2007) in the soil without and with 50 kg ha -1 of N, these values surpass the value of 11.9 cm in the capitulum diameter of the sunflower cultivar H358 at the dose of 44.9 kg ha -1 of N reported by Biscaro et al (2008). In this context, Ivanoff et al (2010) claim that adequate N fertilisation management promotes increments of approximately 16% in the mean diameter of sunflower capitulum; this was also observed by Siddiqui et al (2009) …”
Section: Figure 2 Number Of Viable Achenes In Sunflower CV "Embrapamentioning
confidence: 48%
“…Adequate nutritional supply stands out as a criterion for yield and profitability increase in plantations, and N is the macronutrient required in the largest amounts by most crops (LAVRES JUNIOR et al, 2005), mainly because N participates in the formation of proteins, amino acids and other compounds that are vital for plant metabolism. In addition, N plays an important role in the metabolism and nutrition of crops and is the most required nutrient by sunflowers (SACHS et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…O maior número de folhas durante o enchimento de aquênios tem relação direta com o estado nutricional da planta e este, por sua vez, com a produtividade do girassol (Palmer et al, 1996;Biscaro et al, 2008;Ivanoff et al, 2010;Aguiar Neto et al, 2010;Zobiole et al, 2010b). Conforme Zobiole et al (2010b), quando o híbrido BRS 191 foi cultivado em densidade de 42.858 plantas ha -1 , com espaçamento de 70 cm e sem déficit hídrico e nutricional, uma quantidade de 35 folhas, 0,8 m 2 de área foliar e 2 m de altura, foi imprescindível para obter altas produtividades de aquênios.…”
Section: Introductionunclassified
“…A sensibilidade à baixa concentração do nitrogênio e do fósforo também promove o decréscimo da altura e do diâmetro do caule (Prado & Leal, 2006;Ivanoff et al, 2010). Desta forma, avaliações dos caracteres agronômicos durante a fase vegetativa e reprodutiva associadas ao estado nutricional podem explicar melhor o desempenho da produtividade das cultivares em competição.…”
Section: Introductionunclassified
“…If the doses varied from 0 to 120 kg ha -1 , the magnitudes of the responses would probably be higher, especially for the interval from 0 to 30 kg ha -1 of N and P 2 O 5 , due to the very low contents of available P and organic matter in the soil of the experimental area. In the study of Eltz et al (2010), P 2 O 5 doses between 40 and 80 kg ha -1 were sufficient to reach sunflower grain yield of 2,000 kg ha -1 , whereas Ivanoff et al (2010) observed yield of 1,639 kg ha -1 with N fertilization of 60 kg ha -1 , split into 30% at planting and 70% as top-dressing.…”
Section: Bmentioning
confidence: 87%